2021
DOI: 10.1111/ajt.16747
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of short-duration antiviral prophylaxis for hepatitis C positive donor kidney transplants

Abstract: Trials describing 4-to 12-week courses of direct-acting antiviral drugs (DAAs) to treat hepatitis C virus (HCV) transmission from infected donors to uninfected kidney transplant recipients (D+/R− transplants) may be limited in "real-world" application by costs and delayed access to DAAs. We previously reported HCV transmission of 13% among D+/R− transplants with 2-to 4-day pangenotypic sofosbuvir/velpatasvir (SOF/VEL) perioperative prophylaxis, where one patient with HCV transmission was a nonresponder to firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
(99 reference statements)
0
18
0
Order By: Relevance
“…Sexual transmission of HCV is more rare but can occur 27 . Given the rapid reduction in recipient viral loads following initiation of DAA therapy, this case series underscores the importance of instituting DAA therapy as early as possible following HCV D+/R– transplantation 1,28–30 . When DAAs have been used prophylactically (initiated immediately prior to transplantation), recipients had much lower peak viral loads; in some cases, viremia was never detectable 1,17,28 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Sexual transmission of HCV is more rare but can occur 27 . Given the rapid reduction in recipient viral loads following initiation of DAA therapy, this case series underscores the importance of instituting DAA therapy as early as possible following HCV D+/R– transplantation 1,28–30 . When DAAs have been used prophylactically (initiated immediately prior to transplantation), recipients had much lower peak viral loads; in some cases, viremia was never detectable 1,17,28 .…”
Section: Discussionmentioning
confidence: 91%
“…27 Given the rapid reduction in recipient viral loads following initiation of DAA therapy, this case series underscores the importance of instituting DAA therapy as early as possible following HCV D+/R-transplantation. 1,[28][29][30] When DAAs have been used prophylactically (initiated immediately prior to transplantation), recipients had much lower peak viral loads; in some cases, viremia was never detectable. 1,17,28 It is possible that the risk of athome transmission to a caregiver could be eliminated if recipient HCV viremia was cleared prior to hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Because the SVR 12 rate in the DAPPeR trial was suboptimal, the investigators conducted the REFORM HEPC trial by extending the prophylactic SOF/VEL to 8 days with or without ezetimibe combination in 50 participants. The SVR 12 rates increased to 94% and 97% in participants receiving SOF/VEL with and without ezetimibe combination [ 95 ]. Patient tolerance was excellent in both trials (Table 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because the antiviral responses with prophylactic or preemptive DAAs are nearly 100%, there have been no clinical trials to evaluate the efficacy and tolerance of SOF/VEL/VOX for HCV-negative recipients who received HCV-positive kidneys. Only five patients who received SOF/VEL/VOX for 12 weeks, of whom three relapsed in DAPPeR and REFORM HEPC trials, were reported in real-world studies, which showed an overall SVR 12 rate of 100% (Table 4 ) [ 91 , 92 , 95 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown a low transmission rate of 4% with a prophylactic perioperative 7-d DAA regimen ( ±ezetimibe) for "kidney-only" transplants. 5 Ezetimibe, a cholesterol-lowering drug, was used, as it has been shown to restrict HCV entry in hepatocytes in a humanized mouse model. 6 Here, we present our early experience using the same strategy for simultaneous kidney/ pancreas transplants (SKPT), where the risk of transmission is conceivably higher because of a cumulative higher HCV load delivered with dual-organ transplantation.…”
mentioning
confidence: 99%